Effects of Repeated Intravitreal Aflibercept Injection on the Corneal Endothelium in Patients With Age-Related Macular Degeneration: Outcomes From the RE-VIEW Study. Issue 5 (May 2018) - Lass, Jonathan H.; Benetz, Beth Ann; Menegay, Harry J.; Tsipis, Constantinos P.; Cook, Jane Caty; Boyer, David S.; Singer, Michael; Erickson, Kristine; Saroj, Namrata; Vitti, Robert; Chu, Karen W.; Moini, Hadi; et al.
Abstract : Purpose: The effects of repeated intravitreal aflibercept injection (IAI) on the corneal endothelium were studied in patients with unilateral neovascular age-related macular degeneration. Methods: RE-VIEW was a phase 4, open-label, single-arm, multicenter study. Patients received IAI every 8 weeks after 3 monthly doses. Slit-lamp biomicroscopy was performed at all study visits. The central corneal endothelial health was evaluated by specular microscopy in the treated versus untreated fellow eyes at baseline and weeks 24 and 52. Results: No slit-lamp abnormalities were noted in 154 enrolled patients (eyes). Baseline versus 52-week mean (±SD) endothelial morphometric values (n = 118) for the treated versus untreated fellow eyes were respectively as follows: endothelial cell density was 2410 ± 364 versus 2388 ± 384 cells/mm 2 at baseline and remained unchanged at 2401 ± 353 versus 2376 ± 364 cells/mm 2 at 52 weeks ( P = 0.87); the coefficient of variation was 33.5 ± 4.4% versus 34.0 ± 5.0% at baseline and remained unchanged at 34.2 ± 4.7% versus 34.1 ± 4.9% at 52 weeks ( P = 0.18); the percentage of hexagonal cells was 59.5 ± 5.8% versus 59.6 ± 6.4% at baseline and remained unchanged at 59.5 ± 6.0% versus 59.5 ± 5.8% at 52 weeks ( P = 0.96). Conclusions: Repeated IAI for 52 weeks had no apparent corneal endothelial toxicity noted on specular microscopy in patients treated for neovascular age-related macular degeneration. Abstract : Supplemental Digital Content is Available in the Text.Assessment of corneal endothelial safety by analyses of sequential specular microscopic images from patients with unilateral neovascular AMD receiving repeated intravitreal aflibercept demonstrated no significant difference in cell density, CV, and percentage of hexagonal cells between treated and untreated fellow eyes at baseline and 52 weeks. Corneal endothelial safety of intravitreal aflibercept is supported.